Nutrient Amendments of Inorganic Fertiliser and Oil Palm Empty Fruit Bunch and Their Influence on Bacterial Species Dominance and Degradation of the Associated Crude Oil Constituents - Ainon, Hamzah; Siti NurSyazana, Md Salleh; Wong, Kok Kee; Sarmani, Sukiman (Taylor & Francis, 2016)
The effects of inorganic commercial fertiliser (N:P:K = 8:8:1) and oil palm empty fruit bunch (EFB) as nutrient amendments for crude oil degradation and microbial population shift by a microbial consortium [Pseudomonas sp. (UKMP-14T), Acinetobacter sp. (UKMP-12T), Trichoderma sp. (TriUKMP-1M and TriUKMP-2M)] were assessed. The bacterial populations present during crude oil degradation were analysed by spread plate method and 16S rRNA sequences, whereas the presence of fungi was assessed by growth on potato dextrose agar. Crude oil degradation analysed using gas chromatography-flame ionisation detection showed total petroleum hydrocarbon reduced between 70 and 100%, depending on the type of amendments compared to control (≈55%) after 30 days of incubation. Nutrient amendments using NPK fertiliser or EFB were found to influence the domination of different bacterial species, which in turn preferentially utilised different hydrocarbons. This study suggested different nutrient amendments could be used to preferentially select bacteria to degrade different components of crude oil, particularly pertaining to the recalcitrant phytane. This information is very useful for application of in situ bioremediation of soil hydrocarbon contamination.